2001
DOI: 10.1001/archopht.119.10.1487
|View full text |Cite
|
Sign up to set email alerts
|

Topical Treatment of Acute Adenoviral Keratoconjunctivitis With 0.2% Cidofovir and 1% Cyclosporine

Abstract: To evaluate the efficacy of 0.2% cidofovir eyedrops and 1% cyclosporine eyedrops administered 4 times daily (qid) to treat acute adenoviral keratoconjunctivitis.Methods: A randomized, controlled, double-masked study was conducted on 39 patients with acute adenoviral keratoconjunctivitis of recent onset. Patients were divided into 4 treatment groups: (1) cidofovir qid, (2) cyclosporine qid, (3) cidofovir+cyclosporine qid, and (4) sodium chloride qid (control). The diagnosis was confirmed using adenoviral polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 20 publications
0
52
0
3
Order By: Relevance
“…EKC is highly contagious, has a tendency to occur in epidemics, and has been reported worldwide such as epidemic outbreaks in hospitals, swimming pools, military bases, schools, and other community settings; in Asia, this disease is endemic [41][42][43][44][45]. In 1955, Jawetz et al [25] were the fi rst to attribute the etiology of EKC to the infection of ocular surface tissue caused by HAdV.…”
Section: Adenovirus: Biology Classification and Associated Diseasesmentioning
confidence: 99%
“…EKC is highly contagious, has a tendency to occur in epidemics, and has been reported worldwide such as epidemic outbreaks in hospitals, swimming pools, military bases, schools, and other community settings; in Asia, this disease is endemic [41][42][43][44][45]. In 1955, Jawetz et al [25] were the fi rst to attribute the etiology of EKC to the infection of ocular surface tissue caused by HAdV.…”
Section: Adenovirus: Biology Classification and Associated Diseasesmentioning
confidence: 99%
“…There is an anecdotal report of the potential effectiveness of 0.2% cidofovir eye drops in a patient with adenoviral conjunctivitis (91), but a larger study failed to show a statistically significant effect of topical 0.2% cidofovir on the course of the acute phase of adenoviral conjunctivitis (98). Eye drops of 1% cidofovir did prove effective in the prevention of severe corneal opacities and, concomitantly, caused inflammation of the eyelids and conjunctiva (99).…”
Section: Downloaded Frommentioning
confidence: 99%
“…One study found accelerated subjective improvement of local symptoms with 1% cyclosporine eyedrops (4 times a day for 21 days), as Treatment in acute adenoviral keratoconjunctivitis L Asena et al compared with 0.2% cidofovir or a combination of 0.2% cidofovir+1% cyclosporine. 20 In our study, we observed that patients receiving topical corticosteroids experienced the symptoms for a shorter period of time when compared with the palliative treatment group. The mean time until the resolution of the subjective symptoms was significantly higher in patients receiving only artificial tears and palliative treatment (13.3 ± 4.2 days), when compared with patients receiving topical 2% Cyclosporine A (11.2 ± 4.9 days) and topical 1% prednisolone acetate (9.5 ± 4.9 days).…”
Section: Discussionmentioning
confidence: 52%
“…Although there are reports that show the efficacy of topical CsA (1 and 2%) in decreasing the incidence of corneal opacities and in the therapy of active subepithelial infiltrates during the chronic phase, [11][12][13]19,20 there are no studies reported to compare the safety and efficacy of topical Cyclosporine A with topical corticosteroids and palliative treatment in acute adenoviral keratoconjunctivitis. Therefore, we aimed to compare the clinical outcome with different treatment regimens including topical corticosteroids, Cyclosporin A and exclusively palliative therapy, in a large group of patients who admitted to two tertiary eye care centers.…”
Section: Introductionmentioning
confidence: 99%